Analisis profitabilitas PT. Campina ice cream industry tbk - Syarifah, Syarifah; Anwar, Anwar; Wardhana H, M. Ilham (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the financial performance of PT. Campina Ice Cream Industry Tbk. The type of research used is descriptive quantitative. The population in this study is the financial statements of PT. Campina Ice Cream Industry Tbk for 5 (five) periods, namely 2017-2021. Data analysis techniques using the Balanced Scorecard method include profitability ratios. The results of this study indicate that based on the Balanced Scorecard the company's financial performance is in a balanced position. Judging from the value of Return On Equity (ROE) is in poor criteria caused by a decrease in net profit from own capital. Judging from the Return On Asset (ROA) value is in good criteria caused by an increase in net income from the company's total assets. Judging from the value of Net Profit Margin (NPM) is in good criteria caused by an increase in net profit from sales. Judging from the value of the Operating Profit Margin (OPM) is in the poor criteria caused by the decline in operating profit from sales made by the company.